Heap leach modeling: Analysis and optimization with CFD technology - Diane McBride (IMPC 2018 - 29th International Mineral Processing Congress, 2019)
Heap leaching is well-established as a relatively low-cost and low-energy method of extracting metals from low grade ores. However, the design methodology, attention to the engineering details during heap construction and the long time scale in metal recovery makes the process susceptible to significant variation in the success of a heap leach operation. Often the laboratory predicted recovery rates are not achieved on site due to poor understanding of the complex physics of flow and coupled solid-liquid-thermal reactions within the multi-dimensional heterogeneous ore body. Given the large scale of commercial operations, small changes in metal recovery can substantially change the operating profitability. While there are a variety of approaches to heap leach modeling, computational fluid dynamics (CFD) modeling coupled with leach kinetic models offers a methodology to describe and understand the complexities of heap leaching. The CFD model uses leach kinetics specific for the mineralogy of the ore, including gangue chemistry, and provides an energy balance to calculate and predict temperature. Coupled with the CFD model's inherent capability for modeling complex fluid flow, the physics and the chemistry of the heap can be simulated. This provides a tool for engineering design, as well as forecasting heap production under different scenarios. The calibrated model is used to simulate a three-dimensional test heap under fluctuating meteorological data, such as precipitation events, periodic solution application, and notably temperature. These simulations provide support for a methodology to design and engineer heap leaching of low grade copper sulfide ore.